Whole-genome resequencing reveals genomic variation and dynamics in Ethiopian indigenous goats - Sheriff, Oumer; Ahbara, Abulgasim M.; Haile, Aynalem; Alemayehu, Kefyalew; Han, Jian-Lin; Mwacharo, Joram M. (Frontiers in Genetics, 2024)
Ethiopia has about 52 million indigenous goats with marked phenotypic variability which are the outcomes of natural and artificial selection. Here, we obtained whole-genome sequence data of three (Arab, Fellata, and Oromo) Ethiopian indigenous goat populations from northwestern Ethiopia and analyzed their genome-wide genetic diversity, population structure and signatures of selection. We included genotype data from four other Ethiopian goat populations (Abergelle, Keffa, Gumuz, and Woyto-Guji), and goats from Asia, Europe, and eastern, southern, western and northern Africa to investigate the genetic predisposition of the three Ethiopian populations and perform comparative genomic analysis. Genetic diversity analysis showed that Fellata goat exhibited the lowest hetrozygosity values (Ho = 0.288 ± 0.005 and He = 0.334 ± 0.0001). The highest values were observed in Arab goat (Ho = 0.310 ± 0.010 and He = 0.347 ± 4.35e-05). Higher inbreeding coefficient (FROH = 0.137 ± 0.016) was recorded for Fellata goat compared to 0.105 ± 0.030 of Arab and 0.112 ± 0.034 of Oromo goats. This indicates that Fellata goat population should be prioritized in future conservation activities. The three goat populations showed their majority (~ 63%) of ROH in the shorter (100-150 Kb) length category, illustrating ancient inbreeding and/or small founder effect. Population relationship and structure analysis separated the Ethiopian indigenous goats into two distinct genetic clusters lacking phylogeographic structure. Arab, Fellata, Oromo, Abergelle and Keffa represented one genetic cluster. Gumuz and Woyto-Guji formed a separate cluster and share a common genetic background with the Kenyan Boran goat.Genome-wide selection signature analysis identified nine strongest regions spanning 163 genes influencing adaptation to arid and semi-arid environments (HOXC12, HOXC13, HOXC4, HOXC6 and HOXC9, MAPK8IP2), immune response (IL18, TYK2, ICAM3, ADGRG1, ADGRG3), and production and reproduction (RARG, DNMT1). Our results provide insights into a thorough understanding of genetic architecture underlying selection signatures in Ethiopian indigenous goats under semi-arid tropical environment and deliver valuable information for goat genetic improvement, conservation strategy, genome-wide association study and marker-assisted breeding.